Barriers of Online Learning during the Covid-19 Pandemic : A Factor Analysis Study - Akbar, Fuad Husain; Aziz, Sharifah Noorhidayah Syed; Krishnan, Vijayaletchumy; Othman, Mohd Khairul Fitri; Ismail, Maymunah; Haron, Muhd Zulhilmi; Bahadin, Siti Azura (CENTRAL ASIA AND THE CAUCASUS, 2022)
Background: One method of learning that was born from the development of technology ise-learning. During the Covid-19 pandemic online learning applied almost in all educational institutions in the world and become the main learning method replacing conventional methods, one of the tertiary institutions in Indonesia which applies online learning during the pandemic was Hasanuddin University.Aim: To explainanalysis of factors related to implementation barriers online learning during the COVID-19 pandemic at Hasanuddin University students.Method: A cross sectional design with a population of students at Hasanuddin University with snowball sampling technique. This research was conducted at starting from 4-10 July 2020. This research tool is an online questionnaire in the form of Google.Results: The results of the independent t-test and the Anova test found that a significant p value (<0.05) was in the experience variable following the online class before the Covid-19 pandemic and the faculty of science.Conclusion: Male gender rated the barriers higher than women, students who had never taken online classes before the pandemic rated barriers higher than they had before, the faculties in the social sciences group and the humanities rated the barriers highest compared to the faculties of other science groups.